Stylistically Coloured Lexis and Artistic Speech - Yu., Zueva N.; M., Tayeva R. (Farabi Journal of Social Sciences, 2019)
Abstract. A special place in the structure of the Russian language is taken by colloquial elements in the literary bookish language. The principles of constructing colloquial speech approximate it to the language of belles-lettres. Of interest is the problem of reflecting the colloquial speech of different social layers in a work of fiction: it refers not only to characters’ direct, dialogical speech, but also to special features of colloquial speech which are used as signals of represented speech, the narrator’s speech and speech of the author close to personages. The writer YuryTrifonov skillfully uses common colloquial and newly created lexemes for his heroes’ typification.